Maternal Death Cause by Antepartum Eclampsia, With HELPP Syndrome and AKI Stage III : A Preventable Recurrent Death - Ferry Yusrizal; Fitria Koeshardani; Agustina H; Zulkhair Ali; Junaidi A (HM Publisher, 2021)
Background: Eclampsia and severe preeclampsia is of the most frequent cause of maternal death. We usually find the case like this in our daily practice. The case most likely could be prevented. Eclampsia defined as a generalized seizure following preeclampsia in pregnancy. Eclampsia/Preeclampsia (EPH-Gestosis) cause a multisystem dysfunction such as HELLP syndrome, microangiopathy hemolytic anemia, liver dysfunction, and thrombocytopenia. Eclampsia and HELLP syndrome lead to maternal mortality, which happened mostly during third trimester. Most of the patient came to the hospital in a bad condition where the multi organs failure were exist. EPH-Gestosis are due to maternal death in 43,75%. Even the case usually severe, it’s a preventable death. A proper strategy is needed to reduce or to avoid the maternal death.Objective: To analyse a maternal death with eclampsia and how to prevent this recurrent death.Case Report: A woman, 30 years old, G2P1A0 32 weeks pregnant not in labor with antepartum eclampsia was admitted to Mohammad Hoesin General Hospital (MHGH) Palembang, a referral case. Patient experienced generalized seizure six times before coming to MHGH which every seizure duration is less than five minutes and unconscious. On physical examination, patient was conscious, with blood pressure of 160/100 mmHg, pale, and cold extremities. By ultrasound examination, it showed 34 weeks pregnancy with single life fetus. Laboratory examination showed leukocytosis (25.000/mm3), thrombocytopenia (58.000/mm3), hyperbilirubinemia, elevated SGOT and SGPT (1691 and 861 U/L), elevated creatinine serum (2,46 mg/dl), and elevated LDH (3629 U/L). The patient was treated based on the protocol for stabilization with intramuscular injection of MgSO4 40%, nifedipin 10 mg per oral, intravenous injection of dexamethasone 12 mg, and plan to terminate the pregnancy by caesarean procedure. The male baby was born, 2000 g weight and APGAR score 4/6/8. After the cesarean the consciousness not so well. Collaborating therapy to handle the case, with the anesthesiologist, internist and neurologist. Maternal death occurred in 3 days hospitalized …caused by multi organ failure (MOF). Conclusion: The maternal death caused by antepartum eclampsia and the complication. The diagnosis of antepartum eclampsia and HELLP syndrome was decided based on history taking, physical examination, and supporting examination. Multiple organ failure exist in this case when the patient came to MHGH. Patient already treated and tried to overcome the complication but maternal death still occurred. This maternal death has a likely same story of previous death pattern. It is needed a strategy to prevent or to reduce the maternal death and how to make a good effort to cease the case become severe or worst.